“Knowledge Society for All”: A critical analysis to the visions of the German and Ecuadorian states - Ruiz Andrade, Michelle Anai (2016)
In correlation to the development of communication technologies, the possibilities to access, share, generate, and even commoditize knowledge have significantly increased throughout the last three decades. Relying on a public-private agreement, governments are disposed to optimize their strategy to manage knowledge. Both discourses are comparatively analyzed by focusing on the contextualization and interpretation of each enterprise’s planning of a Knowledge Society, which symbolic ordering has been institutionalized on key documents. The inquiry questions whether this paradigm contributes to the diminishment or reinforcement of epistemological hierarchies and, therefore, whether it challenges or deepens socio-economic, as well as cultural gaps.